Distinct representations of syllables and phonemes in Chinese production: Evidence from fMRI adaptation. (October 2015) - Yu, Mengxia; Mo, Ce; Li, You; Mo, Lei
Abstract: Existing linguistic theories have converged on the fundamental role of syllable and phoneme as the phonological production units that drive articulation in most alphabetic languages, while much remains controversial concerning the logographic Chinese because there is no conclusive evidence of the neural correlates of syllabic and phonemic processing during Chinese speech production. Here, fMRI adaptation paradigm was used to explore the possibility of distinctive neural representations of phonemes and syllables when native Chinese speakers pronounced Chinese pseudowords. We found that bilateral basal ganglia (BG) exhibited evident neural adaptation effect for phonemic repetition, indicating independent neural representation of phonemes in the speech production network in Chinese speakers. Moreover, neural adaptation effect for syllabic repetition was found in bilateral superior temporal gyrus (STg). These findings thus suggest that, similar to alphabetic languages, both phonemes and syllables are phonological production units associated with distinctive neural representations in Mandarin Chinese and further implicate the universality of hierarchical phonological coding across different linguistic systems. Highlights: Neural adaptation effect was induced by phoneme and syllable repetition in Chinese. BG and STg are tuned to Chinese phoneme and syllable respectively. Both phoneme and syllable are phonological production units in spoken Chinese. Phonological structure of Chinese is hierarchically organized as alphabetic languages.